Factorial Design Analysis for Localization Algorithms - Mass-Sanchez, Joaquin; Ruiz-Ibarra, Erica; Gonzalez-Sanchez, Ana; Espinoza-Ruiz, Adolfo; Cortez-Gonzalez, Joaquin (Applied sciences, 2018)
Localization is a fundamental problem in Wireless Sensor Networks, as it provides useful information regarding the detection of an event. There are different localization algorithms applied in single-hop or multi-hop networks; in both cases their performance depends on several factors involved in the evaluation scenario such as node density, the number of reference nodes and the log-normal shadowing propagation model, determined by the path-loss exponent ( η ) and the noise level ( σ d B ) which impact on the accuracy and precision performance metrics of localization techniques. In this paper, we present a statistical analysis based on the 2 k factorial methodology to determine the key factors affecting the performance metrics of localization techniques in a single-hop network to concentrate on such parameters, thus reducing the amount of simulation time required. For this proposal, MATLAB simulations are carried out in different scenarios, i.e., extreme values are used for each of the factors of interest and the impact of the interaction among them in the performance metrics is observed. The simulation results show that the path-loss exponent ( η ) and noise level ( σ d B ) factors have the greatest impact on the accuracy and precision metrics evaluated in this study. Based on this statistical analysis, we recommend estimating the propagation model as close to reality as possible to consider it in the design of new localization techniques and thus improve their accuracy and precision metrics.